Meningkatkan Hasil Belajar Peserta Didik melalui Metode Problem Based Learning berbantuan Media Video pada Siswa Kelas IV Fase B di SD Negeri 17 Nusa Poring Kab. Melawi - Melkianus Jaham; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The low learning achievement of students in working together and overcoming subject matter problems related to daily life in Catholic Religion and Character lessons causes the achievement of learning outcomes to be low. The aim of this Classroom Action Research is to: determine the increase in the dimensions of mutual cooperation and learning achievement in learning using the Problem Based Learning Method. This classroom action research is divided into four stages, namely planning, implementation, evaluation and reflection and is carried out in 2 cycles. The research subjects were students at SD Negeri 17 Nusa Poring with a total of 10 students. Indicators for observing aspects of the mutual cooperation dimension are caring, collaboration and sharing. The results of the research showed that there was an increase in the learning outcomes of Class IV students in the material "I Developed My Abilities as a Man and a Woman, namely an increase in the dimensions of mutual cooperation character using the PBL method from cycle I, which was 65% to cycle II, which was 90%. There was also an increase in the average learning achievement in cycle 1 from 70% to 87% in cycle II. Conclusion: The dimensions of mutual cooperation in the learning process using the PBL method are able to increase the achievement target at a proficient level of 90%, proficient 10% worthy of 0%, just developing 0%.